The Righteous Mind: Why Good People Are Divided by Politics and Religion by Jonathan Haidt - Bauer, Henry H. (Journal of Scientific Exploration, 2012)
This book has had much favorable publicity, including author interviews on radio and TV. Those snippets indicated that anomalists might derive useful understanding from the book, seeing as we’re divided from mainstream science by something like ingrained ideologies. But I found the book immensely disappointing, for after 300+ pages, the conclusions amount to this: • We are heavily influenced by gut feelings—hardly a revelation; I was nurtured intellectually on Freud’s scenario of interactions between id, ego, and superego, and the general idea of conscious and unconscious or subconscious minds. • People of different backgrounds or cul tures tend to differ on many issues. • We tend to regard those who differ with us as being not only wrong but even immoral. • People who have established points of meaningful commonality are better able to discuss other matters agreeably. I don’t know how long ago it was that I reached those conclusions without wading through a textbook that charts in considerable detail the development of the field of moral psychology and the author’s own participation in it, which is what this book is. The academic slant, which includes abstraction and a tendency to overgeneralize, is illustrated for example by: the human mind is designed to ‘do’ morality. (p. xii) an obsession with righteousness (leading inevitably to self-righteousness) is the normal human condition. (p. xiii) human beings—but no other animals—. . . produce large cooperative groups, tribes, and nations without the glue of kinship. (p. xiii)